Looking Beyond the Church: The Religious Crisis of Dutch Public Life During the 1960s - Kennedy, James (Journal of religion in Europe, 2012)
Many parts of Western Europe and North America experienced as Hugh McLeod has noted a ‘religious crisis’ in the 1960s. Yet, this multifaceted ‘religious crisis’ did not affect ‘the church’ alone, as McLeod's work strongly suggests. Politics and civil society also changed substantially. Hit particularly hard by the change in religious sensibilities was the Netherlands, where half the population went to church regularly until the mid-1960s, after which attendance declined rapidly. More than in most other parts of Western Europe, rapid religious change brought about a serious crisis to the institutions of Dutch society. This article seeks to explore the dynamics of traversing the transition from a ‘Christian country’ to a ‘civilised society’ in the course of the Dutch 1960s. In the Netherlands, that transition was relatively rapid and in some respects went further than elsewhere. At the same time, the changes also afforded religious civil society and politics continued opportunities for public presence. In looking at the Netherlands, this contribution hopes to problematize and make new distinctions in McLeod's typification of the 1960s as a decade that hit primarily ‘the churches,’ opening the way to consider the role of other kinds of ‘religious actors’ in this crucial decade, and in its aftermath.